(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the multifaceted role of bilingualism in English language teaching within the multilingual context of Uzbekistan. Drawing on both quantitative and qualitative data, the research investigates how bilingual strategies—specifically code-switching and translation—impact cognitive development, pedagogical effectiveness, and sociocultural inclusivity in the EFL classroom. Sixty participants (40 students and 20 teachers) from two higher education institutions were involved in surveys, classroom observations, interviews, and assessments. The findings indicate that bilingual approaches significantly enhance vocabulary acquisition (82%), speaking fluency (75%), and student engagement (88%) compared to monolingual instruction. From a cognitive perspective, the strategic use of students’ first language (Uzbek) supports metalinguistic awareness and problem-solving. Pedagogically, bilingual strategies help clarify complex structures and reduce learner anxiety, while socioculturally, they validate students’ linguistic identities. However, over-reliance on L1 remains a challenge, emphasizing the need for a balanced approach. The study recommends integrating bilingual methods into teacher training and curriculum design, with gradual transitions toward English-only instruction as learners’ proficiency improves.